Strategies for Enhancing Education Quality Through Digitalization Towards World Class Education at Universitas Pendidikan Indonesia Bumi Siliwangi’s Partner Schools - Sri Kadarsih; Kasful Anwar Us; Fridiyanto , Fridiyanto (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
In response to the global urgency for education systems to adapt to the demands of the 21st century, this study examines strategic efforts to enhance education quality through digitalization at Universitas Pendidikan Indonesia (UPI) Bumi Siliwangi’s partner schools. As nations strive to develop competitive and future-ready human capital, integrating digital technologies into school systems has become a critical pathway toward achieving World Class Education. This research investigates how digital tools—such as Learning Management Systems, multimedia platforms, and online communication applications—are utilized to transform learning processes, administrative operations, and stakeholder engagement. Key enablers identified include visionary leadership, ongoing professional development, infrastructure readiness, and collaborative support from UPI. However, challenges such as digital inequality, varying levels of digital literacy, and resistance to change highlight the need for systemic and sustainable strategies. The findings emphasize that advancing digitalization is not merely a technical upgrade but a cultural shift, requiring long-term commitment and policy alignment to ensure inclusive, high-quality education for all learners.